Studies on The Growth and Biochemical Activity of Coleus aromaticus Benth. as Influenced by AM Fungi and Azospirillum - M. Panneerselvam, M. Lenin, P. Thamizhiniyan (Recent Research in Science and Technology, 2009)
Mycorrhizal fungi are obligated symbiotic soil fungi which colonize the roots of the majority of plants. These fungi help to ensure an opportunity for the utilization of the symbiosis and contribute to the success of sustainable medicinal plants. To a large degree, mycorrhizas seems to be symbiotic relationships, in which the fungus obtains at least some of its sugars from the plant, while the plant benefits from the efficient uptake of mineral nutrients by the fungal hyphae. Coleus aromaticus Benth. (Lamiaceae), commonly called Indian Borage, is a medicinal plant and several medicinal properties are attributed to this plant in the Indian system of medicine. The study was conduct to evaluate the morphological parameters such as root length, shoot length, fresh weight, dry weight, total leaf area and root nodules was measured. The biochemical viz., chlorophyll ‘a’ and ‘b’ total chlorophyll, protein, starch and amino acid contents were tabulated. The higher growth and biochemical content was observed the inoculation of AM fungi + Azospirillum applied plants when compared with control plants.